PEMILIHAN SUPPLIER THERMAL INSTULATION MENGGUNAKAN METODE FUZZY ANALYTIC HIERARCHY PROCESS DAN TOPSIS PADA PT ATP - Gervaies, Charles; Ahmad; Doaly, Carla Olivia (Universitas Tarumanagara, 2024)
Supplier selection is a very important thing in purchasing activities for companies to improve product quality. PT ATP is having difficulty choosing the best supplier. One of the methods used in supplier selection is the Fuzzy Analytic Hierarchy Process (FAHP) method which is a method for solving a complex, unstructured situation into several components in a hierarchical arrangement, by giving subjective values about the relative importance of each variable, and in set variables. Based on the analysis of the selection of the highest ranking supplier for rockwool suppliers, namely PT. KNC with a weight of 0.471, PT. AI with a weight value of 0.331, and PT WIP with a weight value of 0.198. Meanwhile, for aluminum alloy products, the supplier PT. HIC with a weight of 0.698, PT. VII with a weight value of 0.215, PT SAI with a weight value of 0.008, and PT. MTS. The results from Fuzzy AHP show that the highest ranking for rockwool suppliers is PT. KNC with a weight of 0.471, PT. AI with a weight of 0.331, and PT WIP with a weight of 0.198. Meanwhile, for aluminum alloy, the best supplier is PT. HIC (0.698), PT. VII (0.215), PT SAI (0.008), and PT. MTS (0.079).